EFEKTIFITAS PENAMBAHAN TEPUNG RIMPANG TEMULAWAK (Curcuma xanthorrhiza Roxb ) DAN TEMU PUTIH (Curcuma zedoria Rosc) DALAM RANSUM TERHADAP High Density Lipoprotein (HDL), Low Density Lipoprotein (LDL) DAN BERAT ORGAN DALAM PADA AYAM BROILER - Tuli, Noldy; Nangoy, freddy; Tangkere, evacuree; Tangkau, Linda (Universitas Sam Ratulangi, 2014)
An experiment was conducted to examine the effectiveness of curcuma xanthorrhiza Roxb and curcuma zedoria Rosc flours added in Ration on High density lipoprotein (HDL), low density lipoprotein (LDL) and the viscera of broiler. Fifty-four of broiler CP 707Â® strain were used in this experiment and they were placed into cages (60cm x 45cm x 45cm), 3 birds per cage. There were 18 bulb lamp of 25 watt above each cages. Randomized completely design were used in this experiment; 3 treatments and 6 repetitions. The three treatments were R0 (ration without Curcuma xanthorrhiza Roxb and Curcuma zedoria Rosc flours ration with), R1 (ration with 2% of Curcuma xanthorrhiza Roxb flours added in ration, and R2 (2% of Curcuma zedoria Rosc flours). The blood HDL level of broilers in this experiment were 133,58mg/dl (R0), 113,33mg/dl (R2) and 109mg/dl (R1), respectively. The blood LDL level of broiler were 45,66mg/dl (R0), 56,33mg/dl (R2) and 64,66mg/dl (R1), respectively. By using Chi square test, it showed that, there was a relations of addition of 2% of Curcuma xanthorrhiza Roxb and Curcuma zedoria Rosc flours in ration with blood HDL level. However, there was not a relation of addition of 2% of Curcuma xanthorrhiza Roxb and Curcuma zedoria Rosc flour in ration with blood LDL level. In short, the addition of 2% of Curcuma xanthorrhiza Roxb and Curcuma zedoria Rosc flours in ration were not efectively increased the level of HDL and not efectively decreased the level of LDL in blood. Furthermore, the percentage of gizard weight, percentage of pancreas weight, percentage of small and large intestine weight of broiler in this experiment were not significantly different between treatments (P>0,05).